Where Does International Entrepreneurship End? Exploring Entrepreneurial Exit from Internationalised SMEs through Trade Sales - Davenport, Sally (School of Management Working Papers, 2009)
International entrepreneurship is of great current interest with governments increasingly turning their attention to supporting the internationalisation of small and medium-sized enterprises (SMEs) in order to increase international competitiveness. The international entrepreneurship literature is primarily focused on entry mode with subsequent performance of the SME usually being linked back to entry decisions rather than to the firm’s subsequent growth strategies. We argue that an international entrepreneurship framework should extend further post-entry and, given the emphasis in the field on the entrepreneur, ultimately to the drivers for their exit from the internationalised firm. In an exploratory study of ten internationalised New Zealand SMEs, it was found that the entrepreneurs exited at a stage when the internationalised firms had reached a barrier to further growth, which was resolved through a trade sale to a multi-national enterprise. Institutional factors in the New Zealand domestic environment resulted in the trade sale as a favoured exit strategy. Policy implications for the home nation are discussed given the sale is a form of inward foreign direct investment. A policy conundrum arises in that the best approach to countering such trade sales may be to support outward foreign domestic investment by the internationalised SME. The paper suggests that the exit of the internationalising entrepreneur should be considered as one boundary marker between international entrepreneurship and international business.